2014
DOI: 10.1007/s12024-014-9550-y
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine injuries in suicidal hanging without a long-drop—patterns and possible underlying mechanisms of injury: an autopsy study

Abstract: Cervical spine injuries are not commonly found in short-drop suicidal hanging, occurring in only 3.3 % of all observed cases. Cervical spine injury may be occurring in 80 % of subjects aged 66.5 years and above. The most common pattern of cervical spine injury included anterior longitudinal ligament disruption of the lower cervical spine, disk space widening, and no vertebral body displacement. These injuries were mainly associated with an anterior knot position, and may be a consequence of loop pressure to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
17
0
3
Order By: Relevance
“…Cervical spine injuries are considered rare in suicidal hanging ranging from 0% to 9.9% (Table ). They are more common in judicial type hanging where long drop is a factor.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine injuries are considered rare in suicidal hanging ranging from 0% to 9.9% (Table ). They are more common in judicial type hanging where long drop is a factor.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the GCS on outcome is inconsistent in the reported literature. 3,5,6 We found that a GCS < 8 was a predictor of poor outcome but a low GCS was also seen in 52% of patients with a good outcome (Table 1). The motor score component of the GCS, which has not been previously investigated as an independent variable in near-hanging, appears to be a much better indicator of the outcome than the total GCS score, similar to studies in head injury.…”
Section: Discussionmentioning
confidence: 81%
“…Although, hyperextension has been described by majority of authors as the most common neck movement for causing fracture-dislocation, ante-flexion was also found by few (Zhu et al 2000). Nikolic & Zivkovic reported cervical spine injury in a cases of hanging without long-drop pattern with a frequency 3.27% (Nikolic and Zivkovic 2014). But, in his series all the victims were old aged with severe osteoporotic changes in bones.…”
Section: Discussionmentioning
confidence: 93%